2017
DOI: 10.1016/j.celrep.2017.05.064
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic Dynein Transports Axonal Microtubules in a Polarity-Sorting Manner

Abstract: Summary Axonal microtubules are predominantly organized into a plus-end-out pattern.Here, we examined the polarity-sorting mechanism underlying this organization both experimentally and using modeling. The posited mechanism centers on cytoplasmic dynein transporting plus-end-out and minus-end-out microtubules into and out of the axon, respectively. When cytoplasmic dynein was acutely inhibited, the bi-directional transport of microtubules in the axon was disrupted in both directions, after which minus-end-out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(95 citation statements)
references
References 35 publications
2
92
1
Order By: Relevance
“…In support of this model, recent work has demonstrated that after 24 and 48 hours of dynein inhibition with ciliobrevin D, microtubule polarity in rat neurons becomes progressively less organized. 63 Further work with continued observation of microtubule growth and orientation over longer periods following dynein inhibition will be necessary to fully confirm the underlying mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this model, recent work has demonstrated that after 24 and 48 hours of dynein inhibition with ciliobrevin D, microtubule polarity in rat neurons becomes progressively less organized. 63 Further work with continued observation of microtubule growth and orientation over longer periods following dynein inhibition will be necessary to fully confirm the underlying mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…For example, neurofilaments, which provide structural stability to a cell, are transported to the axon terminus by plus end-directed microtubule motors (kinesins 4 ) and to the soma by the minus end-directed microtubule motor, cytoplasmic dynein (hereafter referred to as dynein) [5][6][7] . Dynein has also been shown to play a key role in trafficking numerous other neuronal cargoes in various model organisms [5][6][7][8][9][10][11][12][13][14][15][16][17][18] , including autophagosomes [19][20][21] , mitochondria, and ionotropic glutamate receptors 22 . Defects or perturbations in dynein function lead to mislocalization of these cargoes, and results in an accumulation of protein aggregates at the neurite tip 19,23 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to carrying cargo, dynein also transports, or slides, microtubules (Rao and Baas, 2018). Dynein anchored in the proximal axon translocates microtubules into or out of the axon and prevents the entry of minus-enddistal microtubules (del Castillo et al, 2015;Rao and Baas, 2018;Rao et al, 2017). Our data suggest that dynein also maintains axonal microtubule polarity by excluding Golgi outposts that have the capacity to induce changes in microtubule organization.…”
Section: Loss Of Gm130 Significantly Reduces Misoriented Microtubulesmentioning
confidence: 71%
“…The loss of dynein activity alters both Golgi outpost localization and axonal microtubule polarity (Arthur et al, 2015;del Castillo et al, 2015;Klinman et al, 2017;Rao et al, 2017;Zheng et al, 2008). We first asked whether the misoriented microtubules in dynein loss-of-function neurons depend on the ectopic Golgi outposts.…”
Section: Loss Of Gm130 Significantly Reduces Misoriented Microtubulesmentioning
confidence: 99%